2014
DOI: 10.1183/09031936.00075614
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence and the risk of severe asthma exacerbations: a systematic review

Abstract: The benefits of drug therapy for asthma have been well established, but adherence to treatment is poor, and this might be associated with an increased risk of asthma exacerbations. The aim of this study was to review the literature on the association between adherence to asthma controller treatment and risk of severe asthma exacerbations in children and adults.A systematic literature search was performed in PubMed, Embase and Web of Science, from inception until January 2014. Studies were included if data on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
296
2
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(322 citation statements)
references
References 64 publications
(120 reference statements)
12
296
2
12
Order By: Relevance
“…From adherence studies on chronic medication, it is known that adherence is the highest upon treatment initiation, but decreases rapidly in the first 3-6 months [28][29][30]. MPR calculations and fixed time periods are not ideal to calculate adherence; however, it is a common method used in database studies to estimate drug use [31]. Differences in adherence before and after switch were observed in users of budesonide and beclomethasone, where the median MPR was different after switch, direction depending on the time period, type of medication, and type of switch.…”
Section: Discussionmentioning
confidence: 99%
“…From adherence studies on chronic medication, it is known that adherence is the highest upon treatment initiation, but decreases rapidly in the first 3-6 months [28][29][30]. MPR calculations and fixed time periods are not ideal to calculate adherence; however, it is a common method used in database studies to estimate drug use [31]. Differences in adherence before and after switch were observed in users of budesonide and beclomethasone, where the median MPR was different after switch, direction depending on the time period, type of medication, and type of switch.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence from studies in children and adults suggests that inadequate health literacy is an important key barrier to asthma knowledge [80,81]. Hence, focusing on nonadherence related to health literacy in asthmatic patients may yield benefits in term of both human suffering and economic costs.…”
Section: Health Literacymentioning
confidence: 99%
“…Adherence which is defined as the patient's behaviors regarding recommendations from a health care provider 4 is a crucial factor contributing to the control of asthma. A recent systematic review showed that good adherence to asthma medication is associated with low risk of severe exacerbation 5 . On the contrary, it has been demonstrated that low rate of adherence to asthma controller therapy is a risk factor for admission to the hospital, near-fatal asthma exacerbations, and death from asthma 6,7 .…”
Section: Corresponding Authormentioning
confidence: 99%
“…Less than 50% of children are adherent to this treatment while in the adult population, the adherence is also low with a highly variable range from 30 to 70% depending on the area where the studies have been conducted 5 . In Nigeria, Desalu et al found that 69.3% of their study population had uncontrolled asthma and there was a strong association between uncontrolled asthma and lack of adherence to inhaled corticosteroids 10 .…”
Section: Corresponding Authormentioning
confidence: 99%